2022
DOI: 10.1016/j.jpedsurg.2021.12.046
|View full text |Cite
|
Sign up to set email alerts
|

Early investigations into improving bowel and bladder function in fetal ovine myelomeningocele repair

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 44 publications
0
2
1
Order By: Relevance
“…Our findings for sphincter outcomes differ from those of Farmer et al, who found no differences in bladder function between lambs that underwent fetal MMC repair with cells and control lambs 26 . Our study is the first to show a potentially beneficial effect of UC‐MSCs on urinary function, as lambs that received this treatment showed no incontinence.…”
Section: Discussioncontrasting
confidence: 93%
“…Our findings for sphincter outcomes differ from those of Farmer et al, who found no differences in bladder function between lambs that underwent fetal MMC repair with cells and control lambs 26 . Our study is the first to show a potentially beneficial effect of UC‐MSCs on urinary function, as lambs that received this treatment showed no incontinence.…”
Section: Discussioncontrasting
confidence: 93%
“…[ 25 ] The stem cell therapy alternative, mainly involving stem cells isolated from gestational tissues, have been reported to improve animal survival and guarantee in utero tissue repair in genetically and mechanically induced spina bifida. [ 11 , 26 28 ] Although promising, the inherent risks and hindrances of cell therapy are many and include but are not limited to issues with scalability, cell differentiation abilities and aging, bystander effect which reduces cell potency, number of cells reaching target sites, and therapeutic outcome. [ 29 ]…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, long-term care of these animals to evaluate for this function is difficult given their comorbidities. While the use of anorectal manometry for bowel function evaluation and void volume for bladder function have been reported in the literature, there is currently no standardized evaluation for bowel or bladder function in any of the ovine models of MMC [39].…”
Section: Additional Scientific Rigor To the Modelmentioning
confidence: 99%